2017
DOI: 10.1038/s41598-017-13464-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights into grapevine defense response against drought as revealed by biochemical, physiological and RNA-Seq analysis

Abstract: Grapevine is an important and extensively grown fruit crop, which is severely hampered by drought worldwide. So, comprehending the impact of drought on grapevine genetic resources is necessary. In the present study, RNA-sequencing was executed using cDNA libraries constructed from both drought-stress and control plants. Results generated 12,451 differentially expressed genes (DEGs), out of which 8,021 genes were up-regulated, and 4,430 were down-regulated. Further physiological and biochemical investigations w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 71 publications
6
78
0
Order By: Relevance
“…During ROS metabolism, DEGs associated with the glutathione metabolic pathway were downregulated, such as glutathione peroxidase gene (GPX), glutathione S-transferase gene (GST), glutamate-cysteine ligase gene (GSH), and spermidine synthase gene (SPMS). Glutathione metabolism contributes to the clearance of ROS in P. ostii leaves [14], which is inconsistent with the ROS clearance system under drought stress studied by Chaves et al [40]. This may be due to drought stress exceeding ROS clearance, leading to destruction of glutathione metabolism and increased ROS content.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…During ROS metabolism, DEGs associated with the glutathione metabolic pathway were downregulated, such as glutathione peroxidase gene (GPX), glutathione S-transferase gene (GST), glutamate-cysteine ligase gene (GSH), and spermidine synthase gene (SPMS). Glutathione metabolism contributes to the clearance of ROS in P. ostii leaves [14], which is inconsistent with the ROS clearance system under drought stress studied by Chaves et al [40]. This may be due to drought stress exceeding ROS clearance, leading to destruction of glutathione metabolism and increased ROS content.…”
Section: Discussionmentioning
confidence: 71%
“…GSA is then converted into delta-1-pyrroline-5-carboxylate synthetase (P5CS) by spontaneous cyclization. Finally, proline is synthesized from P5C by P5C reductase (not detected) enzyme [14]. Also, proline contributes to the clearance of ROS [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSP20 family is known for a strong upregulation in response to abiotic stresses (Swindell et al 2007), so the high expression levels of HSP20 found by Liu et al (2012) in leaves of 'Cabernet Sauvignon' and of HSP17.9 found by Carvalho et al (2014) in leaves of 'Touriga Nacional' upon HS were in line with findings from other species. Also, drought stress causes HSP upregulation, as found by Haider et al (2017;Table 1) in leaves of 'Summer Black'. The authors also reported that upregulated DEGs were about twofold as compared to those that were downregulated, modulating defense-related pathways such as ROS defense system but also basic metabolism such as chlorophyll synthesis.…”
Section: Transcriptomic Studies In Stress Response: the Relevance Of mentioning
confidence: 75%
“…Abiotic stresses considerably harbor plant growth and productivity, thus lead to economic losses. The drought severity hampered grapevine productivity and has deleterious impacts on viticulture worldwide [41,42]. Salt stress is one of the severe abiotic stress, while grapevine plants generally modify their physiology to combat salt stress severity [43].…”
Section: Discussionmentioning
confidence: 99%